Disability and disaster risk reduction as an incongruent matrix: Lessons from rural Zimbabwe - Wilfred Lunga; Paradzayi Pathias Bongo; Dewald van Niekerk; Charles Musarurwa (AOSIS (Pty) Ltd., 2023)
Abstract